INVESTIGATION OF SEISMIC BEHAVIOR OF VERTICAL BLOCK TYPE QUAY WALL - Yuksel, Zeynep Tugce; Ozkan Cevik, Esin (YILDIZ TECHNICAL UNIV, 2016)
Block type quay walls are widely used port structures in the world. In this study two types of vertical block type quay walls with different block size exposed to seismic loading were investigated experimentally. The block ratios of Type I and Type II vertical wall models are B/H=2 and 1.5, respectively. Each wall had six blocks. The tests were conducted in the shaking tank with two different harmonic seismic loadings and the behaviors of these two walls were investigated comparatively.
Keywords: Block type structure; quay wall; seismic behavior; shaking tank; Engineering